Systematic Literature Review: Pemanfaatan Aplikasi Geogebra Pada Materi Transformasi Geometri - Rindi Fatmawati; Yahfizham Yahfizham (International Journal of Mathematics and Science Education, 2024)
This study explores the advantages of employing GeoGebra in geometry transformation education. GeoGebra creates an interactive environment, facilitating exploration and enhancing student engagement. Geometry transformations, encompassing translation, rotation, reflection, and dilation, find broad applications in everyday life. The use of GeoGebra aids in comprehending abstract mathematical concepts through dynamic visualization. The Systematic Literature Review (SLR) method is applied with the PRISMA approach to evaluate relevant literature from 2019 to 2023. The research aims to contribute to innovative approaches in mathematics education by leveraging GeoGebra